Equilateral triangle hexagonal array by crossing two one‐dimensional Dammann gratings with 60°. Issue 9 (20th April 2021) - Ye, Zonghao; Liu, Weicheng; Sun, Peng; Jin, Ge; Li, Junjie; Xie, Yongfang; Zhou, Changhe; Jia, Wei
Abstract: In this paper, we demonstrate a new two‐dimensional Dammann grating element to generate equilateral‐triangle hexagonal spot array distribution with equal intensity. This type of grating is constructed by rotating two one‐dimensional Dammann gratings through an angle of 60° to form a triangular hexagonal array illumination. In this work, a 7 × 7 spot array Dammann grating is fabricated by using electron beam lithography. We have verified the equilateral triangle hexagonal array in experiment, and measured the total diffraction efficiency of the grating up to 52%, with uniformity of 0.29. The new two‐dimensional Dammann grating with its high performance opens avenues for three‐dimensional measurement, electronic toll collection and other applications.